Sosialisasi Kegiatan Webinar: Sediaan Farmasi Bentuk Sirup untuk Mengatasi Penyakit Maag - Widjaja, Herman; Aryanilo, Aryanilo; Andini, Fazri; Pramesti, Junaida; Abdurohim WK, M. Ihsan; Khoiriza, Syifa Nur (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Ulcer or gastritis is an inflammation of the stomach caused by increased stomach acid or mucosal irritation which is generally triggered by irregular diet, stress, smoking habits, and alcohol consumption. This activity aims to increase public understanding of the use of syrup-form pharmaceutical preparations in gastritis therapy. The webinar was held online through Zoom Meeting with a total of 32 participants, consisting of 24 women and 8 men who are students of the University of August 17, 1945 Jakarta, as well as the general public. Evaluation was carried out through pre-test and post-test using five multiple-choice questions that measured understanding of the advantages of syrup preparations, the function of active substances (antacids and sucralfates), the selection of preparations in dysphagia patients, the mechanism of action, and the components of the formulation. The results of the post-test showed an increase in participants' understanding, including 100% of participants answered correctly about the advantages of syrup preparations over tablets, 88% understood the function of antacids, 92% knew the mechanism of action of sucralfate, and 76% understood the selection of preparations in dysphagia patients. Thus, this activity has proven to be effective in increasing participants' knowledge about the use of syrup preparations for the treatment of gastritis. Emphasis is needed on the aspect of preparing preparation for dysphagia patients and an understanding of the components of the formulation.